Correction: Acridinedione as selective flouride ion chemosensor: a detailed spectroscopic and quantum mechanical investigation. Issue 7 (23rd January 2020) - Iqbal, Nafees; Ali, Syed Abid; Munir, Iqra; Khan, Saima; Ayub, Khurshid; al-Rashida, Mariya; Islam, Muhammad; Shafiq, Zahid; Ludwig, Ralf; Hameed, Abdul
Abstract : Correction for 'Acridinedione as selective flouride ion chemosensor: a detailed spectroscopic and quantum mechanical investigation' by Nafees Iqbal et al., RSC Adv., 2018, 8, 1993–2003.